A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia - Márquez, Roberto; Mejía-Vargas, Daniel; Palacios-Rodríguez, Pablo; Ramírez-Castañeda, Valeria; Amézquita, Adolfo (Zootaxa, 2017)
Northwestern South America is among the most biodiverse, albeit unexplored, regions of the world. The genus Andinobates is made up of 14 species, all distributed in Northwestern South America (Colombia and Northern Ecuador), and adjacent Panamá. Within the last decade, five species of this genus have been described. In this paper we describe yet another species, belonging to the Andinobates fulguritus group, from the Urabá region of Northwestern Colombia. The new species can be distinguished from other members of Andinobates on the basis of a unique combination of coloration, size, and advertisement call parameters. Molecular phylogenetic and genetic distance analyses corroborate the species’ taxonomic affinity, and further support its status as a distinct lineage. Finally, we discuss the implications of our findings on the systematics of the A. fulguritus group.